Effect Numbered Head Together Based on Agrarian Ethnomathematics on Students’ Mathematical Communication Skills - Dian Qurratul Aini; Abd Aziz; Eka Rahayu (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematics instruction needs to be designed contextually so that students are not only able to solve problems but also able to communicate mathematical ideas, strategies, and reasoning clearly. One relevant approach is the Numbered Heads Together (NHT) cooperative learning model, integrated with agrarian ethnomathematics as a context closely related to students’ lives. This study aimed to analyze the effect of implementing an agrarian ethnomathematics-based NHT model on students’ mathematical communication skills in linear programming. The study employed a quantitative approach with a quasi-experimental nonequivalent control group pretest-posttest design. The participants were 11th-grade students at SMA Istiqlal Sumber Centeng, Kotaanyar, Probolinggo, consisting of 26 students in the experimental class and 25 students in the control class. Data were collected through an essay test designed to measure indicators of mathematical communication and were analyzed using normality tests, homogeneity tests, and an independent samples t-test. The results showed that the data were normally distributed and homogeneous, and that there was a significant difference between the two groups, with a p-value of less than 0.001. The mean score of students’ mathematical communication skills in the experimental class reached 84.31, which was higher than that of the control class, at 76.92. This improvement was supported by the use of agricultural contexts, such as land planning and crop yield optimization, which helped students understand mathematical concepts more meaningfully. These findings indicate that integrating NHT with agrarian ethnomathematics can serve as an effective contextual learning approach.